Detailed analysis of therapy-driven clonal evolution of TP53 mutations in chronic lymphocytic leukemia - Malčíková, Jitka; Staňo Kozubík, Kateřina; Tichý, Boris; Kantorová, Barbara; Pavlová, Šárka; Tom, Nikola; Radova, L; Šmardová, Jana; Pardy, Filip; Doubek, Michael; Brychtová, Yvona; Mráz, Marek; et al. (Leukemia, 2015)
In chronic lymphocytic leukemia (CLL), the worst prognosis is associated with TP53 defects with the affected patients being potentially directed to alternative treatment. Therapy administration was shown to drive the selection of new TP53 mutations in CLL. Using ultra-deep next-generation sequencing (NGS), we performed a detailed analysis of TP53 mutations' clonal evolution. We retrospectively analyzed samples that were assessed as TP53-wild-type (wt) by FASAY from 20 patients with a new TP53 mutation detected in relapse and 40 patients remaining TP53-wt in relapse. Minor TP53-mutated subclones were disclosed in 18/20 patients experiencing later mutation selection, while only one minor-clone mutation was observed in those patients remaining TP53-wt (n=40). We documented that (i) minor TP53 mutations may be present before therapy and may occur in any relapse; (ii) the majority of TP53-mutated minor clones expand to dominant clone under the selective pressure of chemotherapy, while persistence of minor-clone mutations is rare; (iii) multiple minor-clone TP53 mutations are common and may simultaneously expand. In conclusion, patients with minor-clone TP53 mutations carry a high risk of mutation selection by therapy. Deep sequencing can shift TP53 mutation identification to a period before therapy administration, which might be of particular importance for clinical trials.
Keywords: mutace; dospělí; Tumor Suppressor Protein p53; Recurrence; Female; Adult; ženské pohlaví; Leukemia, Lymphocytic, Chronic, B-Cell; High-Throughput Nucleotide Sequencing; buněčné klony; lidé; Survival Analysis; Antineoplastic Agents; protinádorové látky; recidiva; signální transdukce; Mutation; klonální evoluce; Signal Transduction; regulace genové exprese u leukemie; retrospektivní studie; Male; Aged; vysoce účinné nukleotidové sekvenování; nádorový supresorový protein p53; B-Lymphocytes; analýza přežití; Gene Expression Regulation, Leukemic; B-lymfocyty; lidé středního věku; Clone Cells; senioři; mužské pohlaví; Clonal Evolution; Retrospective Studies; Middle Aged; chronická lymfatická leukemie; Humans